Qingdao Port Cardiovascular Health Study: a prospective cohort study. Issue 12 (9th December 2015) - Spatz, Erica S; Jiang, Xianyan; Lu, Jiapeng; Masoudi, Frederick A; Spertus, John A; Wang, Yongfei; Li, Xi; Downing, Nicholas S; Nasir, Khurram; Du, Xue; Li, Jing; Krumholz, Harlan M; et al.
Abstract : Purpose: In China, efforts are underway to respond to rapidly increasing rates of heart disease and stroke. Yet the epidemiology of cardiovascular disease in China may be different from that of other populations. Thus, there is a critical need for population-based studies that provide insight into the risk factors, incidence and outcomes of cardiovascular disease in China. The Qingdao Port Cardiovascular Health Study is designed to investigate the burden of cardiovascular disease and the sociodemographic, biological, environmental and clinical risk factors associated with disease onset and outcomes. Participants: For this study, from 2000 through 2013, 32 404 employees aged 18 years or older were recruited from the Qingdao Port Group in China, contributing 221 923 annual health assessments. The mean age at recruitment was 43.4 (SD=12.9); 79% were male. In this ongoing study, annual health assessments, governed by extensive quality control mechanisms, include a questionnaire (capturing demographic and employment information, medical history, medication use, health behaviours and health outcomes), physical examination, ECG, and blood and urine analysis. Additional non-annual assessments include an X-ray, echocardiogram and carotid ultrasound; bio-samples will be collected for future genetic and proteomic analyses. Cardiovascular outcomes are accessed via self-report and are actively being verified with medical insurance claims; efforts are underway to adjudicate outcomes with hospital medical records. Findings to date: Early findings reveal a significant increase in cardiovascular risk factors from 2000 to 2010 (hypertension: 26.4–39.4%; diabetes: 3.3–8.9%; hyperlipidaemia: 5.0–33.6%; body mass index >28 m/kg 2 : 14.1–18.6%). Future Plans: We aim to generate novel insights about the epidemiology and outcomes of cardiovascular disease in China, with specific emphasis on the potentially unique risk factor profiles of this Chinese population. Knowledge generated will be disseminated in the peer-reviewed literature, and will inform population-based strategies to improve cardiovascular health in China. Trial registration number: NCT02329886.